Efficient and selective removal of Pb2+ from aqueous solution by using an O− functionalized metal–organic framework. Issue 26 (22nd June 2022) - Jiang, Wen; Yu, Cai-Xia; Yu, Ming-Xuan; Ding, Jing; Song, Jian-Guo; Sun, Xue-Qin; Liu, Lei-Lei
Abstract : A novel Pr(iii )-MOF decorated with O − groups was elaborately constructed and showed good performance in removing Pb 2+ . Abstract : Lead (Pb) is one of the most widespread and highly toxic heavy metals in the environment. The design and synthesis of adsorbent materials for the selective and efficient removal of Pb 2+ from aqueous solution has received much attention. Herein, the ligand 4, 4′-azoxydibenzoic acid with the O − group was elaborately selected to construct a novel Pr-based MOF for Pb 2+ removal. The as-prepared MOF adsorbents with high stability exhibited ultra-high selectivity for Pb 2+, even in the presence of various highly concentrated competitive ions (with the ratios from 1 : 5 to 1 : 50). Also, a high uptake capacity (560.26 mg g −1 ) can be achieved for the MOF material, due to the availability of sufficient adsorption sites. The strong electrostatic attraction and coordination interaction between the numerous active O − sites on MOF adsorbents and Pb 2+ can account for the good adsorption performance for Pb 2+, which was systematically verified by zeta potential, FT-IR and XPS studies.